2004
DOI: 10.1128/jcm.42.7.3023-3029.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Microflora Associated with Dental Caries

Abstract: Molecular techniques have revealed many novel, presumed unculturable, taxa in oral infections. The aim of this study was to characterize the bacterial community of the middle and advancing front of carious dental lesions by cultural and molecular analyses. Samples were collected with a hand excavator from five teeth with carious lesions involving dentine. Samples were cultured on blood agar and Rogosa agar incubated in air plus 5% CO 2 and on fastidious anaerobe agar anaerobically. DNA was also extracted direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

34
259
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(298 citation statements)
references
References 27 publications
34
259
2
3
Order By: Relevance
“…Isolates of O. uli and O. profusa are regularly recovered from disease sites in the human mouth (Munson et al, 2002(Munson et al, , 2004Hooper et al, 2006) and sometimes from blood of humans with local oral or gastrointestinal infections (Lau et al, 2004;Bahrani-Mougeot et al, 2008). Olsenellae are found in the healthy (Ozutsumi et al, 2005;Cho et al, 2006;Hernandez et al, 2008) and acidotic (Tajima et al, 2000) bovine rumen.…”
mentioning
confidence: 99%
“…Isolates of O. uli and O. profusa are regularly recovered from disease sites in the human mouth (Munson et al, 2002(Munson et al, , 2004Hooper et al, 2006) and sometimes from blood of humans with local oral or gastrointestinal infections (Lau et al, 2004;Bahrani-Mougeot et al, 2008). Olsenellae are found in the healthy (Ozutsumi et al, 2005;Cho et al, 2006;Hernandez et al, 2008) and acidotic (Tajima et al, 2000) bovine rumen.…”
mentioning
confidence: 99%
“…OTU and culture group numbers are presented here as reported in the original paper. The seven habitats shown are (1) endodontic pathogenic oral biofilms (Munson et al, 2002); (2) exodontic oral biofilms (Munson et al, 2004); (3) Hawaiian lakes and Lō'ihi (Donachie et al, 2004a); (4) rhizoplane (Kaiser et al, 2001); (5) bird feathers (Shawkey et al, 2005); (6) ocean (Eilers et al, 2000); (7) hypersaline salterns (Maturrano et al, 2006). molecular methods alone can detect 'unculturable' (i.e., previously uncultivated) bacteria.…”
mentioning
confidence: 99%
“…In a combined cultural and molecular analysis of the microbiota in dentinal caries, we found that an as-yet unnamed taxon was the dominant Propionibacterium taxon present and was one of only three taxa at species level to be found in every lesion (Munson et al, 2004). The aim of the present study was to perform a genetic and phenotypic characterization of three strains that are representative of this unnamed Propionibacterium taxon.…”
mentioning
confidence: 99%
“…Strains C3M_31 T , C2A_34 and C5A_34 were isolated from the dentine of carious lesions in three subjects, as described previously (Munson et al, 2004). Strains were grown at 37 u C on fastidious anaerobe agar (FAA; LabM) supplemented with 5 % horse blood in an anaerobic workstation (Don Whitley Scientific) under anaerobic conditions (80 % N 2 /10 % H 2 /10 % CO 2 ).…”
mentioning
confidence: 99%